‘VARIAN MUKA LAIN’ Hasil Komunikasi Antar Budaya Di Desa Dungkek, Sumenep - Akhsaniyah Akhsaniyah (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2018)
Sumenep is known as a region that has a diversity of cultures, as well as a harmonious society in maintaining inter-ethnic harmony. This was clearly seen in Dungkek Village, Dungkek Subdistrict, where there were unique characteristics of Madurese and Chinese ethnic communities who for hundreds of years lived peacefully side by side. This is what underlies the author's interest in conducting research in Dungkek, which is focused on how the beginning and development of intercultural communication in Dungkek Village and the process of interaction betweenen Madurese and Chinese cultural identities. This type of research is qualitative using descriptive methods. The researcher used cultural identity theory to decipher the evolving variables of cultural identity, and explained the emergence of the identity of the "Chinese Peranakan" in Dungkek. The results of this study were to give birth to the historical aspects of the birth of Chinese Peranakans in the perspective of cultural identity, as well as formulate patterns / models of intercultural communication that developed in Dungkek. In addition, this research succeeded in identifying supporting factors in building intercultural communication in the Sumenep community style.